E02 The prevalence and factors associated with knee pain in a sample of cyclists within the United Kingdom: A cross sectional study - Braybrooke, Alex; Cooper, Dale (Graduate Journal of Sports Science, Coaching, Management, & Rehabilitation, 2024)
The study aimed to determine: (i) the lifetime and period prevalence of knee pain, (ii) the prevalence and nature of medical attention cycling- related injuries, (iii) and the risk factors associated with knee pain and in a sample of competitive and non-competitive cyclists in the UK. A cross-sectional questionnaire was used to collect data on knee pain, medical attention injuries, and potential risk factors associated with knee pain. Participants were competitive and non-competitive cyclists aged 18 years and older and were recruited through cycling clubs and online advertisement. Binary logistic regression was used to assess for potential risk factors associated with knee pain. Crude and adjusted odds ratios were reported in staged adjustment models, controlling for potential confounders of age and sex. Keele University Ethics Committee approved this study. A total of 115 respondents completed the questionnaire. Lifetime knee pain prevalence was 48%, with period prevalence 26.1% (past-month) and 18.3% (past-week). Aged 40 and over was the only factor found to be associated with knee pain, although this was no longer significant after adjustment for sex. The most prevalent site and type of injury was the lower back and fracture (traumatic), respectively. Knee pain prevalence is high in this sample of cyclists, particularly in those aged 40 years and over. Injury prevention strategies should target the lower back and fractures. Longitudinal research is needed to identify if there are modifiable risk factors that may reduce the occurrence of both knee pain and traumatic fractures in cyclists.